Analisis Implementasi Nilai Pendidikan Karakter Dalam Pembelajaran Pkn di Sekolah Dasar Negeri 07 Banyumudal - Nugrahani, Arum Kusuma; Ysh, A. Y Soegeng; Setianingsih, Eka Sari (STKIP Andi Matappa Pangkep, 2024)
This research aims to analyze the implementation of character education through Civics learning activities at SD Negeri 07 Banyumudal. The type of research used is descriptive qualitative research. The subjects of this research were class IV students at SDN 07 Banyumudal. Data collection techniques use observation, interviews and documentation. The validity of the data was obtained using extended observation and triangulation techniques. The data analysis technique uses interactive model data analysis, namely data collection, data reduction, and conclusion/verification. The research results show that the implementation of Character Education in Civics learning is guided by teaching modules which contain character values at every step of the learning. The implementation of these character values is carried out in three stages, namely the planning, implementation and evaluation stages. The character values contained in Civics learning include religion, tolerance, discipline, democracy, curiosity, national spirit, love of the country, respect for achievement, friendship or communicativeness, and responsibility.